Russian Empire’s Monitoring of Turkish-Kazakh and Dzungar-Kalmyk Diplomatic Relations and It’s Methods of Countering Them in the 1730-1740s - Stepan V. Dzhundzhuzov (RUDN Journal of Russian History)
One of the consequences of Kazakh zhuzes’ and the Kalmyk Khanate’s joining Russia was supposedly their rulers’ abandonment of independent foreign policy. This demand was mainly referred to the abandonment of diplomatic relations with the Ottoman Empire and the Dzungar Khanate. Based on the materials of the Joint State Archive of Orenburg Region and published documents, the author examines the evidence of such connections received by the Collegium of Foreign Affairs and the reaction of the Russian authorities to them. Their analysis shows that the Kazakh and Kalmyk rulers tried to circumvent the ban on diplomatic relations taking advantage of the openness of the steppe borders and insufficient military and administrative resources of Russia’s border provinces. The situation was complicated by the desire of the Dzungar Khanate to stir up separatist sentiments among the steppe peoples close to them in terms of the language or way of life. An objective obstacle to the Turkish-Kazakh and Dzungar-Kalmyk rapprochement was conflicts between Kazakhs and Kalmyks. The reason for the strife was usually theft of horses, cattle or the capture of prisoners initiated by each of the parties. At the same time, representatives of the Kalmyk and Kazakh elites could successfully interact when mutual interests required it, and an example of such interaction in the first half of the 1740s was the mediating mission of the Kazakh rulers to establish contacts between Kalmyk khan's wife Darma-Bala and her Dzungarian relatives. In general, during the 1730-1740s, the Collegium of Foreign Affairs and the Astrakhan and Orenburg governors who carried out its instructions managed to find ways to monitor and counteract Turkish-Kazakh and Dzungarian-Kalmyk diplomatic relations.